The CRISPR-Cas9 crADSL HeLa transcriptome: A first step in establishing a model for ADSL deficiency and SAICAR accumulation - Mazzarino, Randall C; Baresova, Veronika; Zikánová, Marie; Duval, Nathan; Wilkinson, Terry G; Patterson, David; Vacano, Guido N (Molecular genetics and metabolism reports, 2019)
Adenylosuccinate lyase (ADSL) catalyzes two steps in de novo purine synthesis (DNPS). Mutations in ADSL can result in inborn errors of metabolism characterized by developmental delay and disorder phenotypes, with no effective treatment options. Recently, SAICAR, a metabolic substrate of ADSL, has been found to have alternative roles in the cell, complicating the role of ADSL. crADSL, a CRISPR KO of ADSL in HeLa cells, was constructed to investigate DNPS and ADSL in a human cell line. Here we employ this cell line in an RNA-seq analysis to initially investigate the effect of DNPS and ADSL deficiency on the transcriptome as a first step in establishing a cellular model of ADSL deficiency. We report transcriptome changes in genes relevant to development, vascular development, muscle, and cancer biology, which provide interesting avenues for future research.
Keywords: de novo purine synthesis, (DNPS); Adenylosuccinate lyase; RNA-seq; succinyladenosine monophosphate, (SAMP); Transcriptome; phosphoribosylaminoimidazolesuccinocarboxamide, (SAICAR); adenylosuccinate lyase, (ADSL); differentially expressed gene, (DEG); aminoimidazole carboxamide ribonucleotide, (AICAR); fragments per kilobase of exon per million reads mapped, (FPKM); plus adenine crADSL to plus adenine WT comparison, (PP); adenosine monophosphate, (AMP); fetal calf macroserum, (FCM); guanosine monophosphate, (GMP); Purine synthesis; gene ontology, (GO); false discovery rate, (FDR); minus adenine crADSL to minus adenine WT comparison, (MM); phosphoribosyl pyrophosphate, (PRPP)